Cerebrospinal fluid/serum albumin ratio in patients with Lewy body disease: a systematic review and meta-analysis - Li, Moyu; Gan, Jinghuan; Yang, Xia; Liu, Shuai; Ji, Yong (Frontiers in Aging Neuroscience, 2024)
Background Abnormal cerebrospinal fluid (CSF)/serum albumin ratio (Qalb) levels have been observed in patients with cognitive impairment. Few studies have specifically focused on Lewy Body Disease (LBD), and the results were controversial. Thus, we conducted this systematic review and meta-analysis to investigate Qalb levels in patients with LBD by including data from different studies. Method We systematically searched PubMed, Embase, Cochrane Library, and Web of Science databases for a collection of studies containing studies comparing Qalb levels in patients with LBD and healthy controls (including healthy controls and other dementia subtypes). In the initial search, 86 relevant papers were retrieved. Standardized mean differences (SMD) in Qalb levels were calculated using a random effects model. Results A total of 13 eligible studies were included. Mean Qalb levels were significantly higher in patients with LBD compared to healthy older adults [standardized mean difference (SMD): 2.95, 95% confidence interval (CI): 0.89–5.00, Z = 2.81, p = 0.005]; and were significantly higher in patients with LBD than in patients with Alzheimer’s disease (AD) (SMD: 1.13, 95% CI: 0.42–1.83, Z = 3.15, p = 0.002);whereas mean Qalb levels were significantly higher in patients with frontotemporal lobar degeneration (FTLD) compared to those with AD (SMD: 1.13, 95% CI,0.14–2.13, Z = 2.24, p = 0.03). Conclusion Qalb levels were significantly elevated in LBD patients compared with normal older adults and were higher than those in AD patients and FTLD patients, which helped in the differential diagnosis of LBD from other neurodegenerative diseases. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42024496616.